Epigenetic regulation of nuclear receptors: Implications for endocrine-related diseases and therapeutic strategies - Yixin Song; Kexin Zhang; Jingwen Zhang; Qinying Li; Na Huang; Yujie Ma; Ningning Hou; Fang Han; Chengxia Kan; Xiaodong Sun (Genes and Diseases)
The expression and function of the receptor are controlled by epigenetic changes, such as DNA methylation, histone modification, and noncoding RNAs. These modifications play a pivotal role in receptor activity and can lead to or exacerbate endocrine-related diseases. This review examines the epigenetic alterations of nuclear receptors and their significant impact on conditions such as diabetes, thyroid disorders, and endocrine-related tumors. It highlights current therapies targeting these epigenetic mechanisms, including gene editing, epigenetic drugs, and various other therapeutic approaches. This review offers fresh insight into the mechanisms of endocrine-associated disorders, highlighting the latest progress in the development of novel epigenetic therapies that can be used to address receptor–endocrine interactions.